Primary angiosarcoma of thyroid - Kondapalli, Ananya (BMJ Case Rep, 2019)
Mesenchymal origin of primary thyroid angiosarcomas (TAS) is extremely rare and comprises less than 1% of primary thyroid cancer worldwide. While TAS are most commonly occurring in the Alpine region, there are multiple reported cases of TAS in non-Alpine regions. Diagnosis of TAS is commonly made after thyroidectomy as cytologic diagnosis can be challenging due to paucity of cells, presence of necrosis and unawareness of the disease due to rarity. We report a case of primary TAS diagnosed by cytology in a 56-year-old man who presented with a sudden onset of left neck pain, swelling and haemoptysis. He was later noted to have suspicious nodules on both lobes of thyroid on ultrasound. Fine needle aspiration of thyroid nodules showed malignant epithelioid cells. The diagnosis of TAS was made based on positive endothelial markers such as thrombomodulin and CD31, with many pertinent negatives, including negative cytokeratins,thyroid transcription factor (TTF1), thyroglobulin, calcitonin and carcinoembryonic antigen (CEA).